A Phase 1, Placebo-controlled, Randomized, Single Ascending Dose Study and a Volunteer Infection Study to Characterize the Safety, Pharmacokinetics, and Antimalarial Activity of the Plasmodium Phosphatidylinositol 4-Kinase Inhibitor MMV390048. (2nd April 2020) - McCarthy, James S; Donini, Cristina; Chalon, Stephan; Woodford, John; Marquart, Louise; Collins, Katharine A; Rozenberg, Felix D; Fidock, David A; Cherkaoui-Rbati, Mohammed H; Gobeau, Nathalie; Möhrle, Jörg J
Abstract: Background: MMV390048 is the first Plasmodium phosphatidylinositol 4-kinase inhibitor to reach clinical development as a new antimalarial. We aimed to characterize the safety, pharmacokinetics, and antimalarial activity of a tablet formulation of MMV390048. Methods: A 2-part, phase 1 trial was conducted in healthy adults. Part 1 was a double-blind, randomized, placebo-controlled, single ascending dose study consisting of 3 cohorts (40, 80, 120 mg MMV390048). Part 2 was an open-label volunteer infection study using the Plasmodium falciparum induced blood-stage malaria model consisting of 2 cohorts (40 mg and 80 mg MMV390048). Results: Twenty four subjects were enrolled in part 1 (n = 8 per cohort, randomized 3:1 MMV390048:placebo) and 15 subjects were enrolled in part 2 (40 mg [n = 7] and 80 mg [n = 8] cohorts). One subject was withdrawn from part 2 (80 mg cohort) before dosing and was not included in analyses. No serious or severe adverse events were attributed to MMV390048. The rate of parasite clearance was greater in subjects administered 80 mg compared to those administered 40 mg (clearance half-life 5.5 hours [95% confidence interval CI, 5.2–6.0 hours] vs 6.4 hours [95% CI, 6.0–6.9 hours]; P = .005). Pharmacokinetic/pharmacodynamic modeling estimated a minimum inhibitory concentration of 83 ng/mL and a minimal parasiticidal concentration that would achieve 90% of the maximum effect of 238 ng/mL, and predicted that a single 120-mg dose would achieve an adequate clinical and parasitological response with 92% certainty. Conclusions: The safety, pharmacokinetics, and pharmacodynamics of MMV390048 support its further development as a partner drug of a single-dose combination therapy for malaria. Clinical Trials Registration: NCT02783820 (part 1); NCT02783833 (part 2). Abstract : MMV390048 is a promising new antimalarial compound in clinical development. We characterized the safety, pharmacokinetics, and antimalarial activity of MMV390048 in healthy adults. The results support the development of MMV390048 as a partner drug of a single-dose combination malaria therapy.